High rate anaerobic digestion of swine wastewater in an anaerobic membrane bioreactor. (15th February 2020) - Jiang, Mengmeng; Westerholm, Maria; Qiao, Wei; Wandera, Simon M.; Dong, Renjie
Abstract: Efficient treatment of swine wastewater at a high rate would facilitate the development of a sustainable pig industry. In this study, to investigate methane fermentation and membrane filtration performance, an anaerobic membrane bioreactor was operated under mesophilic conditions for 207 days during four stages, with a hydraulic retention time (HRT) decreasing from 5 to 3, 2, and 1 day, and a changing of solid retention time/hydraulic retention time (SRT/HRT) ratio from 18, 18 to 8 and 3.2. The results showed that a higher volumetric methane production of 1.63 L/(L·d) and a lower VFAs concentration (<200 mg/L at stable stage) could achieved when the HRT was 1 day and SRT/HRT ratio was only 3.2. The specific methanogenic activity slightly decreased under the shorter HRT, and with SRT/HRT shortening, hydrogenotrophic Methanocorpusculum tended to dominate in bulk sludge while acetoclastic Methanosaeta dominated in the biofilm. Membrane fouling was observed after 4 months with a flux decline and a significant increase in trans-membrane pressure. A serial cleaning test indicated that organic pollutants contributed highly to the membrane fouling. Graphical abstract: Image 1 Highlights: HRT was successfully reduced to 1 day in the AnMBR. The specific methanogenic activity decreased during the shortening of the HRT. The biofilm attached to the membrane had higher acetoclastic methanogens. Membrane fouling was almost completely removed by sodium hypochlorite.